The Role of Cherry Coffee Ethanol Extract in Repairing Liver Damage in Type 2 Diabetic Rats - Tengku Soraya Putri; Nurfadly Nurfadly; Humairah Medina Liza Lubis (UMSU, 2026)
Abstract:Background. Type 2 diabetes mellitus (T2DM) is a metabolic disorder characterized by chronic hyperglycemia due to insulin resistance and pancreatic β-cell dysfunction. Chronic hyperglycemia triggers oxidative stress and increases inflammation, thereby contributing to liver damage. The potential of coffee cherry ethanol extract as an antioxidant and anti-inflammatory agent could serve as a therapeutic option for improving liver damage. Objective. This study aims to evaluate the effects of coffee cherry ethanol extract on liver histopathology in a T2DM mouse model. Methods. This study used 28 male Wistar rats, divided into 7 groups with 4 rats in each group, administered coffee cherry ethanol extract at doses of 100 mg/kg body weight and 200 mg/kg body weight/day/oral. Results. The results showed that administration of coffee cherry ethanol extract improved hepatocyte structure, reduced inflammatory infiltration, and decreased fat accumulation in liver tissue compared to the untreated DMT2 group (p0.05). Conclusion. Coffee cherry ethanol extract has potential as an adjunct therapy to slow the progression of DMT2 complications in the liver. Further studies are needed to confirm its efficacy, mechanism of action, and long-term effects in humans. Keywords: ethanol extract, liver histopathology, oxidative stress, type 2 diabetes mellitus.